Modeling the impact of calorie‐reduction interventions on population prevalence and inequalities in childhood obesity in the Southampton Women's Survey. (17th May 2021) - Russell, Simon J.; Hope, Steven; Croker, Helen; Crozier, Sarah; Packer, Jessica; Inskip, Hazel; Viner, Russell M.
Abstract: Background: In the United Kingdom, rates of childhood obesity are high and inequalities in obesity have widened in recent years. Children with obesity face heightened risks of living with obesity as adults and suffering from associated morbidities. Addressing population prevalence and inequalities in childhood obesity is a key priority for public health policymakers in the United Kingdom and elsewhere. Where randomized controlled trials are not possible, potential policy actions can be simulated using causal modeling techniques. Objectives: Using data from the Southampton Women's Survey (SWS), a cohort with high quality dietary and lifestyle data, the potential impact of policy‐relevant calorie‐reduction interventions on population prevalence and inequalities of childhood obesity was investigated. Methods: Predicted probabilities of obesity (using UK90 cut‐offs) at age 6–7 years were estimated from logistic marginal structural models adjusting for observed calorie consumption at age 3 years (using food diaries) and confounding. A series of policy‐relevant intervention scenarios were modeled to simulate reductions in energy intake (differing in effectiveness, the targeting mechanisms, and level of uptake). Results: At age 6–7 years, 8.3% of children were living with obesity, after accounting for observed energy intake and confounding. A universal intervention to lower median energy intake to the estimated average requirement (a 13% decrease), with an uptake of 75%, reduced obesity prevalence by 1% but relative and absolute inequalities remained broadly unchanged. Conclusions: Simulated interventions substantially reduced population prevalence of obesity, which may be useful in informing policymakers.